2006
DOI: 10.1093/schbul/sbl030
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Psychological Therapy in Schizophrenia: Conclusions From Meta-analyses

Abstract: Over the past years, evidence for the efficacy of psychological therapies in schizophrenia has been summarized in a series of meta-analyses. The present contribution aims to provide a descriptive survey of the evidence for the efficacy of psychological therapies as derived from these meta-analyses and to supplement them by selected findings from an own recent meta-analysis. Relevant meta-analyses and randomized controlled trials were identified by searching several electronic databases and by hand searching of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
217
0
26

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(255 citation statements)
references
References 153 publications
12
217
0
26
Order By: Relevance
“…Evidence suggests that family interventions are effective at reducing patient psychotic relapse and readmissions (Pilling et al, 2002) as well as relatives' high levels of EE (Pfammatter et al, 2006;Pharoah et al, 2010). However, one key issue around family work is implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that family interventions are effective at reducing patient psychotic relapse and readmissions (Pilling et al, 2002) as well as relatives' high levels of EE (Pfammatter et al, 2006;Pharoah et al, 2010). However, one key issue around family work is implementation.…”
Section: Discussionmentioning
confidence: 99%
“…A fourth (Pilling, Bebbington et al, 2002) found no evidence for any kind of effectiveness. A broader meta-analysis of SST and related psychosocial treatment (Pfammatter et al, 2006) found qualified evidence for effectiveness. A review of the problem solving component in SST (Xia & Li, 2007) found insufficient studies to conduct a quantitative meta-analysis, and did not reach positive or negative conclusions.…”
Section: Outcome Research Methodology and Evidence Basementioning
confidence: 99%
“…A substantial amount of research has demonstrated that providing family interventions can significantly reduce relapse rates of people with psychosis over follow-up periods (Pfammatter et al, 2006;Pharaoh et al, 2006). Family interventions are based on the assumption that a stressful interpersonal environment in which an individual lives can exacerbate psychotic symptoms and lead to premature or more frequent relapse of illness.…”
Section: Family Interventions For Psychosismentioning
confidence: 99%
See 1 more Smart Citation
“…Las intervenciones de psicoeducación combinadas con los medicamentos antipsicóticos han demostrado ser eficaces para incrementar el funcionamiento psicosocial y disminuir la emotividad expresada, 3 la sintomatología clínica, las recaídas y las hospitalizaciones; 22 también han demostrado efectividad en variables más indirectas como el mantenimiento del empleo; 23 se ha reportado que estos resultados dependen en gran medida de que los programas psicoeducativos estén fundamentados en las características y necesidades familiares.…”
unclassified